Presence of pathogenic bacteria in the estuary of Surco River and La Chira beach, Lima, Peru, June 2009 - Osores Plenge, Fernando (2009)
The study of the microbiological quality of sea water in the beaches near any city is of the outmost importance in order to know the potential impact on the health of the population using the coastal areas as playgrounds. The presence of many bacterial species, such as coliforms (Escherichia coli, Klebsiella, Citrobacter-Enterobacter spp.), Enterococci spp, Pseudomonas aeruginosa, Clostridium perfringens, Aeromonas hydrophila, Vibrio parahaemolyticus, and Salmonella spp., tends to correlate with the occurrence of gastrointestinal symptoms (vomiting, diarrhea, nausea or abdominal pain) in bathers as well as in people eating fresh sea products. The study was performed with students from the Microbiology course in Universidad Ricardo Palma Medical School. Random and stratified samples were collected from La Chira beach during June 2009 (winter in Lima). It is worth mentioning that La Chira beach is located next to a water sewage duct that dumps millions of gallons of wasted water directly in the sea. Samples were processed in Microbiology laboratories from the aforementioned university. Using the most probable number method for bacterial concentrations, a very high bacterial load was found in every place sampled, and many Enterobacteriaceae were found in cultures.